Designing Puberty Learning Mobile Application with Gamification for Children Grade 4-6 Based on UI/UX - Lam, Eleonora Jovita Halim; Liman, Sheena Yngre (School of Design Universitas Pelita Harapan, 2025)
Sexuality education and knowledge of puberty in Indonesia are often considered taboo, with misconceptions that it has more negative than positive impacts. The government has yet to implement comprehensive sexuality education in the national curriculum. Research indicates that providing sexuality education significantly reduces the incidence of sexual violence among children. This study employs the Research through Design (RtD) approach, involving iterative cycles of design, prototyping, and testing, to develop a puberty learning mobile application. Methods included literature review, surveys, and interviews with stakeholders, followed by data analysis to create design criteria, prototype testing, and final design development. Results show that although most respondents received some form of puberty education, their knowledge was insufficient, highlighting the need for effective learning tools. The proposed application incorporates gamification, community interaction, and parental guidance features to enhance learning. The study concludes that the interactive and engaging design successfully improves awareness and understanding of sexuality and puberty, with potential for further development.